Study of Three Potential Diagnostic Biomarkers in Nasopharyngeal Carcinoma Samples from Guilan, North of Iran - Moghaddam, Saghi Jani Kargar; Roushandeh, Amaneh Mohammadi; Roudkenar, Mehryar Habibi; Nemati, Shadman; Najafi-Ghalehlou, Nima; Pakzad, Toofan; Hamidi, Masoud (International Archives of Otorhinolaryngology, 2022)
Introduction Finding biomarkers for highly lethal cancers is a priority.Objective The current study was designed to understand the clinical significance of vascular endothelial growth factor (VEGF), latent membrane protein 1 (LMP1), and tumor necrosis factor-α (TNF-α) expression as the biomarkers, and evaluate their correlation with each other, in nasopharyngeal carcinoma (NPC) in the province of Guilan, North of Iran.Methods Gene expression was evaluated in 25 formalin-fixed paraffin-embedded (FFPE) blocks from cases of confirmed NPC and 20 FFPE samples of non-NPC by quantifying messenger ribonucleic acid (mRNA) and protein levels, using real-time polymerase chain reaction (PCR) and immunohistochemistry (IHC) methods, respectively. Furthermore, the correlations among the protein levels of different genes, along with the patients' demographic characteristics were assessed.Results Our findings on mRNA and protein levels demonstrated that the expression of the LMP1 gene in the NPC group was significantly elevated compared with that of the non-NPC group. In addition, the protein levels in the NPC group indicated a positive and significant correlation between LMP1 and VEGF expression. It was noted that both protein and mRNA levels showed no significant differences in the expression of TNF-α and VEGF genes between the NPC and control groups. Furthermore, there was no significant relationship between the expression of these proteins and the demographic characteristics of NPC patients.Conclusion Overall, a significant increase in LMP1 expression was observed in NPC patients, which may serve as a diagnostic biomarker for NPC. Also, LMP1 might be involved in NPC progression by inducing VEGF gene expression.
Keywords: nasopharyngeal carcinoma; tumor necrosis factor-α; vascular endothelial growth factor-A; biomarkers